STUDENTS’ PERCEPTIONS OF THE USE OF VIDEO AS A MEDIUM OF LEARNING IN SPEAKING CLASS - Sabarun Sabarun; Aris Sugianto; Rika Soraya (PROJECT (Professional Journal of English Education), 2022)
The study was aimed at knowing how students’ perceptions of the use of video as medium of learning in speaking class. Qualitative descriptive was utilized as a research method. The researcher selected 15 students of English Education IAIN Palangka Raya from 3 classes which were chosen 5 students in each class by using purposive sampling. To gain the data, the researcher used interview and documentation. The result showed the students’ perceptions of the use of video as a medium of learning in speaking class had good result.  Most students said the use of video as a medium of learning in speaking class was effective, flexible, and practice medium. It was also able to increase the students’ speaking skill which was called positive attitude. However, two students disagreed the use of video which was called negative attitude. They mentioned video was ineffective in increasing speaking fluency and not too challenging. Keywords:  Students’ Perceptions, Video, Speaking Class